Supportive Supervision: Meeting to Build Interdisciplinary Teams in the Northern Central Regional Office of the CEN CINAI - Georgianella Araya-Alegría (Revista Electrónica Educare)
This article is the result of a participatory action research project aimed at providing a novel approach for the Northern Central Regional Office of the CEN CINAI [Education and Nutrition Centers (CEN) and the Children’s Nutrition and Comprehensive Care Centers (CINAI)] to build knowledge on an unfinished process: “Supportive Supervision” (supervisión capacitante).  Based on a naturalistic premise, we tried to answer a question that guided us in the group creation and transformation, switching our meetings from a vertical standpoint to a horizontal relationship providing accompaniment, support and construction, as well as analysis and reflection. The article shows the aspects that justified the development of the participative action research process under a methodological proposal that involves those of us who participated and contributed to build knowledge with our experience and from different locations within the Region.  A total of 29 professionals participated, willing to jointly meet a purpose: construct knowledge based on team work and on a process full of uncertainty that encourages us to constantly revise what has already been built and enables us to re-read and retake what has already been written and to systematize what could not be written before. In order words, to make this process a new way of developing knowledge that implies a more concrete standpoint to understand what “Supportive Supervision” is and how it is done, with the purpose of always looking for improvement within the National Directorate of CEN CINAI.